Does partisanship really affect on FDI? An analysis of the Euro Area's FDI policies to Southeast Asian countries - Warokka, Ari; Badrudin, Rudy (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
Foreign direct investment (FDI) is a key element of the global economy. FDI is an engine of employment, technological progress, productivity improvements, and ultimately economic growth. Because of these significant benefits, attracting FDI has become one of the integral parts of economic development strategies in many countries. There are two schools of thought that hypothesize the FDI determinants: economic factors and political factors. For the latter school of thought, the central questions are: Is there a noticeable difference among political parties in a country in their trade policy positions? Do left parties advocate different trade policies than right parties? In the advanced industrial countries where labour tends to be scarce, are left parties more protectionist than right ones, which represent capital owners? Prior evidence had demonstrated an association between partisanship and trade policies (FDI policies).This paper extends the cross-country and temporal variance in national regulation of FDI. The theory looks at government partisanship, which we define in terms of left parties or right parties. The paper tests two hypotheses that explore various aspects how the parties in Euro Area and Southeast Asian countries have competed over trade policy. This study uses 11 Euro Area countries and 5 Southeast Asian countries that actively do outward and inward FDI. The time frame of analysis is 2000-2006 period that is believed as a start of Economic Integration in the European Union, which is symbolized with the launching of European Single Currency at that time. Statistic methods used for testing the hypothesis are t-test and multivariate regression model. The empirical results provide support for an intuitively positive effect of globalization that makes left parties and right parties converge on its political economy and preference into open or free trade. After controlling for various factors, partisanship does not matter. In terms of position taking, both types of partisanship consistently take the free trade stances. In other words, it can be believed that Euro Area and Southeast Asian governments‘ preference on political economic and FDI are becoming more symmetric over time.